UJI TAPIS BRUSELLOSIS PADA SAPI DI RPH OEBA KOTA KUPANG DENGAN MENGGUNAKAN UJI RBT - Eni Rohyati; Noviantie N Toelle; Erda Rame Hau (Politeknik Pertanian Negeri Kupang, 2018)
The aim of this research is detecting Brucella abortus reactor in Rumah Potong Hewan (RPH) Oeba, Kupang City has been carried out using RBT serological test with RBT kits produced by Pusvetma. 105 serum samples were collected randomly from cattle in RPH Oeba in 2018, with details of 7samples from bulls and 98 samples from female cattle, and have been used for this study. All samples were collected with additional data of gender. The results showed that 60 samples were positive and 45 gave negative results. Serum samples that are positive for RBT mostly come from female cattles which are 56 and only 4 bulls gave positive results. The average prevalence is 57%, the majority of the RBT test results from positive samples on the RBT test is +1 scoring (the lowest score in the RBT test).